Transforming Islamic Education Through Eco-Pedagogy: Strategic Leadership of Kiai in Pesantren - Siti Aminah; Muhammad Suwignyo Prayogo (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
The increasing severity of global environmental crises demands educational responses that are not only technical but also value-based and transformative. Islamic educational institutions, particularly pesantren, possess strong moral and spiritual resources to cultivate ecological awareness, yet empirical studies examining eco-pedagogy within pesantren leadership remain limited. This study explores the transformation of Islamic education through eco-pedagogy under the strategic leadership of the kiai at Pesantren Ra’iyatul Husnan Wringin Bondowoso. Eco-pedagogy in this study is understood as an educational praxis integrating critical consciousness, ethical responsibility, and environmental stewardship rooted in Freirean pedagogy and Islamic values. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving the kiai, pesantren administrators, teachers, and students during November-December 2025. Data were analyzed using an interactive model supported by triangulation and member checking. The findings reveal that eco-pedagogical transformation occurs through three interconnected stages: strategic formulation of an ecological vision by the kiai, participatory implementation through curriculum integration and daily practices, and institutionalization via habituation, exemplary leadership, and institutional regulations. This process fosters ecological awareness, emotional attachment, learning motivation, and a strong institutional identity as an environmentally friendly pesantren. The novelty of this study lies in integrating Freirean eco-pedagogy with the strategic and spiritual leadership of the kiai, demonstrating how Islamic education can become contextual, transformative, and sustainable through value-based leadership.